2010
DOI: 10.1017/s1041610210000177
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dementia and mild memory impairment (MMI) on intimacy and sexuality in spousal relationships

Abstract: Early therapeutic interventions may assist couples in modifying activities, behaviors, and expectations about the future of the relationship. Such modifications may help maintain relationship satisfaction, decrease burden, preserve quality of life, and delay time-to-placement. Extending time-to-placement could have cost savings implications for families and the healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0
18

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(106 citation statements)
references
References 40 publications
4
84
0
18
Order By: Relevance
“…Eles se tornam mais egocêntricos e menos flexíveis, com diminuição da expressão verbal e alterações da personalidade -rigidez, apatia, controle emocional debilitado. 9,14 Casais com relação estável e funcional antes do diagnósti-co da demência ressaltaram significativa mudança nas expressões efetivas com o início do comprometimento da memória do cônjuge, relacionando-se à perda do poder de decisão por parte dos pacientes e à mudança de papéis do cônjuge, que assume função parental, com comprometimento das dimensões emocional e sexual do casal. 9,12 No contrário, a interferên-cia da doença parece ser maior.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Eles se tornam mais egocêntricos e menos flexíveis, com diminuição da expressão verbal e alterações da personalidade -rigidez, apatia, controle emocional debilitado. 9,14 Casais com relação estável e funcional antes do diagnósti-co da demência ressaltaram significativa mudança nas expressões efetivas com o início do comprometimento da memória do cônjuge, relacionando-se à perda do poder de decisão por parte dos pacientes e à mudança de papéis do cônjuge, que assume função parental, com comprometimento das dimensões emocional e sexual do casal. 9,12 No contrário, a interferên-cia da doença parece ser maior.…”
Section: Discussionunclassified
“…Problemas de comunicação já existentes entre os parceiros podem ser observados, sobretudo, nos estágios iniciais da doença. 9,10 Problemas de memória e declínio na capacidade de tomada de decisão podem interferir na intimidade, sem diferença significativa entre as demências. 8,9 Em estágios mais avançados da demência, dificuldades em lembrar a sequência apropriada das etapas da relação sexual ou dos passos já realizados levam o paciente a pouco envolvimento com o seu parceiro, pela distração ou perda da excitação ou, ao contrário, à exacerbação da atividade sexual.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La relation avec l'aidé est effectivement un enjeu fondamental du travail de soins mentionné dans plusieurs études (Armstrong-Stassen et Cameron, 2005 ;Gagnon, 2005 ;Gagnon, 2006 ;Pitrou et al, 2006 ;Grosclaude, 2007 ;INPES, 2011). Le degré d'intimité partagée avec l'aidé influera entre autres sur la manière dont sera assumée la responsabilité envers lui (Davies et al, 2010 ;Harris et al, 2011). On parlera de continuité ou de réciprocité relationnelle, ou, au contraire, de détachement ou de sentiment d'obligation de prendre soin (Ablitt et al, 2009).…”
Section: Apport De Cette éTude à La Réflexion Sur La Responsabilité Munclassified
“…For example, a recent review covering the literature up to July 2011, indicated that the most commonly experienced emotions reported by caregivers of individuals with MCI were frustration, guilt, and anger. 8 Other consequences associated with caring for a person with MCI are a strong sense of loss 13 and deprivation in the caregiver relationship with the patient, 14 including less effective communication, a loss of intimacy, 8,15 and decreased marital satisfaction 16 among spouses. Finally, the new responsibilities facing caregivers as a result of the need to compensate for the memory decline in those with MCI take a toll on the caregivers' own lifestyle, for example by reducing the amount of time they have to themselves 17 or for participating in their own recreational activities.…”
Section: Introductionmentioning
confidence: 99%